Increasing Financial Inclusion Through Financial Literacy And Financial Technology On MSMEs - Mimelientesa Irman; Budiyanto Budiyanto; Suwitho Suwitho (International Journal of Economics Development Research (IJEDR), 2021)
The purpose of this research is to identify and understand the influence of financial literacy and financial technology toward financial inclusion of culinary sector MSMEs in Pekanbaru. The sample collection technique is used purposive sampling and obtained sampel about 174 respondent. The research method is used descriptive analysis, preliminary test, regression test, classic assumption test, and hypothesis test by using SPSS 16.0. The result of this research showed that there was a positive and significant influence between financial literacy and financial technology toward financial inclusion of culinary sektor MSMEs in Pekanbaru